Correlation of neurological soft signs with neuropsychological performance in persons with schizophrenia: A cross-sectional study from North-Eastern India - B S Sachin; Kangkan Pathak; Priyaranjan Avinash; Vrinda Saxena; Robin Victor (Archives of Mental Health, 2022)
Background: Neurological soft signs (NSS) are subtle motor and sensory deficits that are frequently found in various psychiatric disorders including schizophrenia. NSS in schizophrenia are frequently associated with impairment in cognitive abilities and deterioration in neuropsychological performance (NP). Objective: We aimed to study the correlation between NSS and NP in persons with schizophrenia. Methods: Sixty individuals of whom thirty had schizophrenia according to the International Classification of Diseases 10th Revision and the rest thirty were matched controls were selected based on inclusion and exclusion criteria. Demographic and clinical details were obtained and tests for the assessment of NSS and neuropsychological assessment were administered. Comparison based on scores obtained in these scales was made in both the groups. Results: NSS were present in 100% of patients with schizophrenia and in 16.6% of controls in the control group. There was a statistically significant difference between the two groups in neuropsychological assessment. In Group 1, NSS showed a significant negative correlation with Tower of London, Stroop Color-Word Test, Digit Vigilance Test, and Digit Symbol Substitution Test. However, there was no correlation between NP and NSS in Group 2. Conclusion: NSS were more in persons with schizophrenia compared to healthy normal controls. Furthermore, there is a negative correlation between NSS and NP in persons with schizophrenia, which is differing from the control group. We may conclude that the presence of NSS predicts the poor NP, and also contributes to poor cognitive abilities of persons with schizophrenia.